TECHNICAL EDUCATION AND DIGITAL MEDIA: AN ANALYSIS OF INSTAGRAM USE IN THE DISSEMINATION OF PHYTOSANITARY KNOWLEDGE - Letticia Ribeiro do Nascimento, Giulliana; Júlia da Costa Pereira Pinto, Ana; Cristina Alba de Souza Sena, Clara; Maria Saldanha de Oliveira, Odiluza; Pereira da Silva Martins, Adriano (Revista Gênero e Interdisciplinaridade, 2026)
This study analyzes the use of Instagram as a tool for disseminating phytosanitary knowledge within the context of Professional and Technological Education (PTE). Grounded in theoretical perspectives on integral education and digital culture, the research investigates the extent to which the integration of technical education and social media can enhance reach and engagement in sanitary education processes. This applied research adopted a qualitative-quantitative approach through a case study conducted in a technical course in Agriculture at a Brazilian federal public institution. The intervention involved the creation and management of an educational Instagram profile focused on phytosanitary content, using multimodal resources such as static posts and short videos (Reels). Data were collected over a 30-day period through Instagram Insights, considering metrics such as reach, interactions, engagement rate, and audience distribution. Results showed significant growth in reached accounts, a high engagement rate (22.5%), and the predominance of short videos in generating interactions. A considerable proportion of engagement came from non-followers, indicating expanded dissemination beyond the immediate school community. The findings suggest that Instagram can function as a complementary pedagogical tool in technical education when supported by structured planning and theoretical grounding, contributing to technological extension and the democratization of scientific knowledge.